Evaluación de la adaptación de variedades de yuca con resistencia a Phytophthora spp., mediante investigación participativa en comunidades indígenas de Mitú (Vaupés, Colombia) - Llano Rodríguez, Germán Alberto; Álvarez, E.; Loke, J; Madriñán, R.; Restrepo, JA; Mora, JR (2001)
Because of land pressure around Mitú (Department of Vaupés, southeastern Colombia), shifting cultivation is no longer practiced with rotation, which had permitted forest regeneration, nor is land adequately selected. These factors have favored the development of cassava pests and diseases, amongst which the most important are root rots, caused by several Phytophthora species. The objective of this work was to evaluate the adaptation of cassava varieties with resistance to Phytophthora spp. to conditions in Mitú, applying participatory research. Through surveys and meetings with the communities there, a crop management diagnostic was made and related to root-rot incidence. Based on the diagnostic, indigenes were asked to evaluate varieties with rot tolerance, and activities were planned with the participation of the communities. With indigenes help, four chagras (farming plots) were chosen in different communities, where 10 CIAT varieties and nine local landraces were evaluated. Using open evaluations, the indigenes defined possible selection criteria for the vegetative stage related to vigor, plant health, plant height, stems per plant, and earliness. The criteria most used at harvest were yield, starch content, and production of cuttings for planting. The identified criteria allowed the elaboration of a field book for future variety evaluations in the zone. The indigenes preferred the CIAT variety CM 2772-3 (sweet, with yellow pulp) to the local landraces. Results were diffused, with local participation, through meetings with departmental institutions, nongovernmental organizations, and communities and through two field days and two illustrated handbooks.